PENGARUH PERPUTARAN KAS DAN PERPUTARAN PIUTANG TERHADAP PROFITABILITAS - ERVITA SAFITRI; BELLIWATI KOSIM; WANI FITRIAH; DARMA YANTI (AKUNTIA JURNAL Jurnal Akuntansi, Terpercaya, Menginspirasi dan Asli, 2022)
This study aims to determine the effect of Cash Turnover and Accounts Receivable Turnover on Profitability in Manufacturing Companies Listed on the Indonesia Stock Exchange. This type of quantitative research because the writer wants to know the effect of the relationship between two or more variables. The population of all Manufacturing Companies listed on the Indonesia Stock Exchange, totaling 180 companies, was then taken as a sample of 19 companies that went public using a purposive sampling method, namely sampling based on certain considerations adapted to the research objectives. Secondary data while data collection techniques using the documentation method. The technique uses multiple linear regression analysis using SPSS version 26 software. Hypothesis testing uses the F test and t test with a significant level of 10%. The results of testing together (test F) shows that there is a significant influence between Cash Turnover and Accounts Receivable Turnover on Profitability. The results of the partial test (t test) show that of the 2 independent variables there are no variables that have a significant effect, namely Cash Turnover does not have a significant effect on Profitability, Accounts Receivable Turnover does not have a significant effect on Profitability